STUDENTS’ PERCEPTIONS TOWARDS DIGITAL TEXT READING - Masagus Sulaiman; Delfi Ambarwati; Indawan Syahri (Universitas Muhammadiyah Makassar, 2021)
ABSTRACTThis research is a survey research in line with finding out the dominant perceptions of UPT students of SMA Negeri 7 Ogan Ilir towards Digital Text Reading. The samples of the research were 87 students, 44 tenth graders and 43 eleventh graders. The researchers used collect the data. To analyze the data, the researchers used percentage analysis. The results showed that the students had positive perception towards digital text reading in their daily life. They often learn and do assignment using digital media because it gives positive experience,motivation and improve reading comprehension achievement. In conclusion, It is comfortable, flexible and helpful to search relevant additional text to study